A Feasibility study on Prince Portable Lifter - Antigua, Marcial III.; Itchon, Concepcion; Laya, Ana Maria; Madamba, Glenford (Diliman, Quezon City College of Engineering, 2000)
The Prince Portable Lifter is an immobile person transport device invented by Dr. Rainier B. Villanueva, a renowned neurosurgeon and internationally recognized inventor. The product is found to relieve inconvenience and discomfort for the patients for it reduces pain compared to traditional methods during transport. There has been too much occurrences of mishandling of patients. The probability of inflicting additional injuries and pain is greater due to the awkward positioning of the patient on any improvised transport device. Based on the market study conducted, it was found out that the demand for the product is present, but because there is no product in the market that is serving the need, the Prince Portable Lifter has no direct competitors. And with an annual sales plan of 3,700, 2,307, 2,336, 2,365, and 2,394 lifters for the first five years of operation, the project will maintain a market share of 68.5% of the industry. The project will be targeting bedridden or immobile patients like 3rd and 4th degree cancer patients and paralysis and/or loss of four limbs orthopedic handicaps who belong to income classes A, B, and C only in the National Capital Region. The product will be distributed using one level method of distribution with a retail price of Php 3,500. Rigorous promotional and advertising campaign will be employed with an estimated budget of Php 974,386 for the first year and Php 434,386 for the succeeding years. The Prince portable Lifter is made up of durable canvas designed to withstand heavy loads. The canvas is fashioned into specific positions onto the canvas to secure the individual to be the natural contour of the normal Filipino body type and size. Velcro straps are attached transported. Likewise, there is a buttock support installed so as the person would not slip out when the person is transferred from the bed to a wheelchair and vice versa. The product is double stitched using durable threads with metal rivets for extra strength and safety. Aluminum bars provide the handles for the lifters. These are slipped in and out of the sides of the canvas. The product will be packaged in a plastic wrapped then placed in a custom made corrugated box. The major processes involved in the manufacture of the lifter include preparation of raw materials, preparation of raw materials, and preparation of aluminum bars, assembly, and packaging. Ten percent (10%) of the inventory of finished goods will be maintained to absorb shocks of fluctuating demand. Based on estimated processing times, 11 lifters can be produced daily in the first year with one 10-hour shift production. 7 lifters can be produced daily in the succeeding years with one 8 hour-shift production. The project will involve only 3 workers directly involved in production and 3 support staff. The plant will be located at Rizal Ave. Extension corner East 4th Ave. Grace Park Caloocan City with an area of 288 square meters which is just enough for the 251square meter space requirement of the project. Total project cost which consists of cost of investment, manufacturing, operating expenses, administrative expenses and 10% contingency amounted to PhP 6,596,596.93. To determine if the three-month operation is adequate to start the project, a total of Php 2,060,773.91 is computed. In establishing the organization of the project, the corporation was chosen to be the most effective. The General Manager would head the organization, which consists of 2 departments, Production, and Accounting and Finance. Some positions in the administrative will be handling multiple functions to maximize the person?s potential. The company would employ 7 administrative and 6 labor personnel. Manpower would be given 13th month pay, SSS, Philhealth and 4% annual increase to their basic salary and wages. From the financial study, the total project cost was reduced to a three-month operation project cost since from the financial statements made, it was revealed that a positive income after tax was obtained on the first year and still remained positive for the three month period. Thus, total project cost amounted to Php 2,060,773.91. Based n an interview with the inventor, a proportion of 60-40 will be employed where 60% of the total cost will be the owner?s equity capital and the remainder of 40% will be shouldered by the stockholders. Results of financial statements, which include income statement, cash flow statement and balance sheet, proved that the project is profitable as evidenced by the increasing net income and positive cash flows. Also based on the ratios obtained from the financial break-even analysis, given a fixed cost of Php 3,558,101.90, a variable cost of Php 1,980,561.30 and a production volume of 2,904 units for the first year and 1,848 units for the succeeding years at a selling price of Php 3,500 per unit, the break-even volumes for the product were computed to be 1,262.64, 1,178.45, 1,276.41, 1,388.05 and 1,516.38 for the first five years respectively. The break-even sales amounted to Php 5,538,663.20, Php 4,660,540.56, Php 4,965,476.70, Php 5,294,624.53 and Php 5,650,153.93. Payback period of the project is 1.31 years or approximately 15.67 months. The net present value (NPV) was Php 3,445,607.01, which is positive or greater than zero, and the internal rate of return (IRR) was 440.9135%, which is greater than the minimum attractive rate of return (MARR) set at 25%. In evaluating the project?s social profitability, its establishment will have several benefits to the society through the community/market, local and national government. Furthermore, there are also qualitative benefits that have been identified. In addition, the project has no significant disbenefits or costs to society. The socio-economic criteria, which are the NPV and IRR, have attractive values. Hence, it can be concluded that the establishment of a company to produce Prince Portable Lifter is an acceptable business venture. After evaluating all the results of the different studies made, the project was determined to be marketable, technically feasible, financially feasible, and socially profitable and the organization and management is also feasible. Thus, the project has met all the necessary requirements to be able to implement the project.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Lifting and carrying; Participatory monitoring and evaluation (Project management)